ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN MEMBELI SEPATU SEPAK BOLA PRODUK DALAM NEGERI - M. Zamroji Almuryid (CV. ADIBA AISHA AMIRA, 2023)
In the current industrial era, competition in various types of businesses has increased very rapidly and is tight, both in terms of goods and services. Competition will also arise in terms of creating new products that are in demand by the public, thus requiring producers to understand the extent to which the behavior shown by consumers in making purchasing decisions for a product made in the country, moreover these products compete with foreign products that have a strong brand image. . The product referred to in this study is a product with the type of soccer shoes where this product is made locally or made by Indonesian children. There are several local brands that are well-known among athletes and people who like to play soccer, one of which is Specs. The research to be conducted is qualitative in nature. In this study more emphasis on descriptive aspects originating from the football community which almost every week organizes internal and external match events. In collecting data, the researchers used data collection techniques by interviewing freely and selecting samples purposively samoling in the community, including comedy F. Based on the results of the research and discussion conducted, it can be concluded as follows 1. Domestically produced shoes that are widely used by community members are ortuseight and specs 2. The driving factor for using domestic shoes with the ortuseight and specs brands is due to the affordable price 3. Convenience when used on all types of football fields 4. Fairly good resilience 5. Models and editions that always keep up with the latest models